(X+41)+95=x+78

Simple and best practice solution for (X+41)+95=x+78 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+41)+95=x+78 equation:


Simplifying
(X + 41) + 95 = x + 78

Reorder the terms:
(41 + X) + 95 = x + 78

Remove parenthesis around (41 + X)
41 + X + 95 = x + 78

Reorder the terms:
41 + 95 + X = x + 78

Combine like terms: 41 + 95 = 136
136 + X = x + 78

Reorder the terms:
136 + X = 78 + x

Solving
136 + X = 78 + x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-136' to each side of the equation.
136 + -136 + X = 78 + -136 + x

Combine like terms: 136 + -136 = 0
0 + X = 78 + -136 + x
X = 78 + -136 + x

Combine like terms: 78 + -136 = -58
X = -58 + x

Simplifying
X = -58 + x

See similar equations:

| 2x+9-x=9+2x-6 | | 74=8(c+4)-4 | | 4760/45= | | 2.5=3.7-0.4x | | 3log(x)=11 | | 5+4x=6x+5-2x | | 8x-1+9x=7x+3-9x | | 2v-13=11 | | f(x)=2x^2+9x-5 | | x=y-0.8 | | 2.6x-1.8y=5.5x-0.8y | | 5x/8-8=x/14+13 | | 5x+9=6(x+2) | | 4y-5=20y+11 | | 3n+yr=r-8h | | -6(3m-5)=-78 | | 2y+4=-6y+10+4y | | x^2+y^2-16*(-2)+8*(-3)-10=0 | | 9(s+8)-23=76 | | 2y+4=8y | | (5x-4+2x^2)(3+4x)= | | 3=-4(4-6p)-(p+4) | | 96=6(v-83)+6 | | y=-32.36x+98.25 | | -5x+29=10x-1 | | -14+x=7 | | 415+X(5)=450 | | 7-(v+3)= | | 4(r+12)-14=82 | | 5x/3-7=23 | | r+2.14=-11.8 | | 4z-4=Z+14 |

Equations solver categories